“SATIETY DISEASES” REDRESSING THE BALANCE BETWEEN ECONOMIC AND SOCIAL DEVELOPMENT IN AZERBAIJAN) - MUZAFFARLI, Nazim (CENTRAL ASIA AND THE CAUCASUS, 2012)
In recent years, sustainable economic development has been an increasingly higher priority for all, both well and less developed, states. The global economic crisis that broke out in 2008 showed that the steadily high growth rates demonstrated by many countries throughout the pre-crisis years, even giving some of them the honorary titles like, for instance, “Celtic tiger,” in actual fact do not always testify to sustainable development. There are economic and social “diseases” that can disrupt, or at least slow down, growth no matter how sustainable it previously seemed. Whereby these diseases can be both internal, that is, determined by trends governing the country’s development, and external, that is, brought in from the outside world, making sustainable economic development not at all what it seemed to be before the crisis. Economic development can be considered fully sustainable if it meets the following three conditions: (a) the economy increases at a stable rate that is sufficiently high for its size and for the given time; (b) it is able to efficiently resist external negative impacts; and (c) it is not oriented toward exclusively current tasks but leaves sufficiently broad opportunities for the future—including with respect to resource distribution. In other words, economic development is sustainable if it is stable, tenable, and long-term. Practical achievement of this sustainability is complicated by the fact that it depends not only on economic factors as such, but also on other components of social development. Conceptually, balanced and harmonious development of the different components of social progress is a mandatory condition of its sustainability as a whole, on the one hand, and of each of these components separately, on the other, whereby in terms of all three parameters of sustainability. We should proceed from the fact that the development curves of different spheres of public life, including the economy, politics, religion, science, education, public health, and culture, wind around the common trunk of social development that forms as their integral result. Should one of these curves ultimately break away from the main trunk (over the span of a hundred years, say), it will be unable to survive independently. Each sphere of social life draws other spheres toward it and tries to bring them to its level of development (higher or lower), which is what causes all the curves to gravitate toward the common trunk. Which curve proves the strongest and is able to attract the others to it depends on a multitude of factors, including its “weight and strength” at a particular historical stage in social development and on how socially important the functions it performs are in public life. The development of the world’s countries and regions abounds in examples that confirm this governing law. We know that in Western Europe, the capitalist economy that came to life in the womb of feudalism eventually gave rise to so-called bourgeois revolutions that raised the political system to the economic level. In the U.S., on the contrary, constitutionally enforced political rights opened the way to economic and then cultural development. A splendid illustration, although of an entirely different nature, is the experience of the Arab world. In the pre-Islamic period, Arab tribes were disunited and extremely backward communities.1 Girls were killed at birth, burying them alive in the desert sand. Along with polygamy, about which much has been said, there was also polyandry, when several (up to ten) men pooled their money to pay for an “extremely expensive” bride and then went into her tent in turn, leaving their staffs propped up outside the door to let the other husbands know that their common wife was currently occupied. The forms of government had only some remote resemblance to statehood.